Fodor's 2009 England. - Fodor's Travel Publications, Inc. (New York : Fodor's Travel Publications, 2009)
A comprehensive travel guide to England, with maps and information on accommodations and restaurants, shopping and entertainment, and interesting sites to visit; and includes Wales.
"Pullout map inside"--Cover.
Spine title: England 2009.
Includes bibliographical references (p. [741]-742), filmography (p. 743-744) and index.
Young Adult
Keywords: England -- Guidebooks; Wales -- Guidebooks; England -- Guidebooks; Wales -- Guidebooks